2017
DOI: 10.1186/s12917-017-1099-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pharmacokinetic–Pharmacodynamic (PK/PD) model to evaluate the in vivo antimicrobial activity of Marbofloxacin against Pasteurella multocida in piglets

Abstract: BackgroundMarbofloxacin is a veterinary fluoroquinolone with high activity against Pasteurella multocida. We evaluated it’s in vivo activity against P. multocida based on in vivo time-kill data in swine using a tissue-cage model. A series of dosages ranging from 0.15 to 2.5 mg/kg were administered intramuscularly after challenge with P. multocida type B, serotype 2.ResultsThe ratio of the 24 h area under the concentration-time curve divided by the minimum inhibitory concentration (AUC24TCF/MIC) was the best PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…To the best of our knowledge, there has been no in vivo PK/PD modeling study of enrofloxacin against E. coli in chicks. One of the best PK/PD parameter for fluoroquinolones is AUC 0–24 /MIC [ 34 36 ], and this study further confirmed this conclusion. Both the surrogate AUC 0–24 /MIC for enrofloxacin or the combination of enrofloxacin and ciprofloxacin correlated well with effectiveness in each organ.…”
Section: Discussionsupporting
confidence: 76%
“…To the best of our knowledge, there has been no in vivo PK/PD modeling study of enrofloxacin against E. coli in chicks. One of the best PK/PD parameter for fluoroquinolones is AUC 0–24 /MIC [ 34 36 ], and this study further confirmed this conclusion. Both the surrogate AUC 0–24 /MIC for enrofloxacin or the combination of enrofloxacin and ciprofloxacin correlated well with effectiveness in each organ.…”
Section: Discussionsupporting
confidence: 76%
“…These three indexes were highly correlated, making it important to have data from several different dosing regimens to be able to distinguish between them. According to the previously published study, it has been demonstrated that AUC/MIC could be regarded as the right and optimal PK-PD index for MBF ( Sidhu et al, 2010 ; Jian et al, 2015 ; Lei et al, 2017a ; Zeng et al, 2017 ). Therefore, the best PK-PD index of AUC/MIC was selected to use for proposing the optimal dose in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The best PK-PD index for a certain drug-bacteria combination is determined by plotting the value of an efficacy endpoint (typically log10 CFU/ml after 24 h of treatment) versus the magnitude of each of the three PK-PD indices. It has been reported that AUC/MIC could be the right and optimal PK-PD index for MBF based on the previously published study ( Sidhu et al, 2010 ; Jian et al, 2015 ; Lei et al, 2017a ; Zeng et al, 2017 ). The best PK-PD index of AUC/MIC was selected to use in this study.…”
Section: Methodsmentioning
confidence: 94%
“…PK/PD models are a vital tool in the analysis of the relationship between the time course and antibacterial effects of veterinary antibacterial agents and, thus, in optimizing a therapy regimen. In order to identify the clinically relevant relationship between the dosage interval time and the effect of a drug, PK/PD modeling, an advanced approach to determining a suitable daily dose and dosage interval, may be used [3738]. Such models have been widely used to establish the dosage regimens of different antimicrobial agents including fluoroquinolones, β-lactam, amphenicols, tetracyclines, aminoglycosides, macrolides, colistin, and valnemulin.…”
Section: Formation Of a Dosage Regimen Via Pk/pd Modelsmentioning
confidence: 99%